'The Ceaseless Labour of Your Life': Occupations and Wages in Holyhead, 1841–81. (1st December 2019) - Huws, Gareth
The relationship between Britain and Ireland in the nineteenth century has been extensively studied, but the crucial significance of the London-Dublin communications link in this relationship has received less attention from historians. This article concentrates on the effect of establishing and maintaining this link on the strategically-placed town of Holyhead and, more specifically, how employment patterns in the town changed as Holyhead became the main mail packet port for the Irish Sea crossing.